The Brazilian Pareiasaur Revisited - Cisneros, Juan C.; Dentzien-Dias, Paula; Francischini, Heitor (Frontiers in Ecology and Evolution, 2021)
Provelosaurus americanus is the only known representative of the Pareiasauria in the Americas. This mid-size pareiasaur from the Rio do Rasto Formation of southern Brazil has been traditionally considered to be related to smaller forms from the South African Karoo known as the ‘dwarf pareiasaurs’ of Lopingian age. P. americanus, however, co-existed with dinocephalians, which indicates a Guadalupian age. New fossils provide a nearly complete osteological account that forms the basis for a revised diagnosis and a test of phylogenetic relationships of P. americanus. Our results offer further support to the hypothesis that the Brazilian pareiasaur is the sister taxon of the Karoo ‘dwarf pareiasaurs’, being the earliest member of this group and one of the oldest pareiasaurs known so far. This is reinforced by a radiometric dating of the Morro Pelado Member of the Rio do Rasto Formation. In addition, the association of four individuals of various ontogenetic stages at the type locality supports some degree of social behavior in P. americanus.